Irreversible electroporation for surgical renal masses in solitary kidneys: short-term interventional and functional outcome - Diehl, Steffen J.; Rathmann, Nils-Andreas; Kostrzewa, Michael; Ritter, Manuel; Smakic, Arman; Schönberg, Stefan; Kriegmair, Maximilian (Journal of vascular and interventional radiology, 2016)
Purpose - To examine short-term outcomes and complications in patients with a solitary kidney treated with irreversible electroporation (IRE) for a potentially malignant renal mass. - Materials and Methods - Five patients (2 female, 3 male; mean age, 66 y) with 7 lesions who underwent IRE for renal tumors in a solitary kidney between August 2014 and August 2015 were retrospectively reviewed. Changes in signal intensity (SI) of the treated lesion were evaluated on contrast-enhanced magnetic resonance imaging. To evaluate functional outcome, creatinine levels and estimated glomerular filtration rate (eGFR) were compared vs baseline after 1 day, 2-7 days, 3-6 weeks, and 6-12 weeks after the intervention. - Results - Mean tumor diameter was 24.4 mm (range, 15-38 mm), with an average score of 7.7 (range, 4-9) per R.E.N.A.L. criteria (radius, exophytic/endophytic, nearness to collecting system or sinus, anterior/posterior, and location relative to polar lines). There was a progressive, significant decrease in treated tumor SI on follow-up imaging (mean, 70%-82%), suggesting a treatment response rate of 100% at a mean follow-up of 6.4 months (range, 3-11 mo). Two minor acute complications (Society of Interventional Radiology class A) occurred: transient gross hematuria and stage I acute kidney failure. Overall, there was no significant decrease in eGFR (−2.75 mL/min) over 3 months, even though 1 patient’s eGFR decreased from > 60 mL/min/1.73m2 to 44 mL/min/1.73m2. - Conclusions - The data suggest that percutaneous IRE for renal mass in patients with a solitary kidney is safe and feasible. It may help to preserve renal function and offers promising short-term oncologic results.